MANAJEMEN PELATIHAN PROFESIONALISME GURU DI SMP NEGERI 17 MAKASSAR - Nur Latifa; Ansar Ansar; Syamsurijal Basri (Jurnal Administrasi, Kebijakan, dan Kepemimpinan Pendidikan (JAK2P), 2022)
The purpose of this study is to find out what Teacher Management Professional Training Management looks like in SMP Negeri 17 Makassar. The approach used in this research is qualitative with descriptive research type. The data sources of researchers are Wakasek Curriculum, Teacher and Teacher BK. and the archive at the research location. Data collection procedures used are interviews, and documentation. The analysis techniques used are data collection, data reduction, data display ,. The results of this study indicate that: The management of this teacher professionalism training includes MGMP training which is an activity to improve professionalism competence as professional educators and develop the quality of education. Teachers must perform optimally and with all efforts to make their students achieve the expected goals. So this paper tries to discuss the management of teacher professionalism training which includes MGMP training as an institution that seeks to produce professional teachers. Besides that, to carry out his professionalism as a professional teacher is his creativity and innovation. Management Teacher professionalism training in Makassar 17 Public Middle School improves the quality of being a professional teacher. Based on good management and management, this training will run according to the desired goals.